How Well the Government of Nepal Is Responding to COVID-19? An Experience From a Resource-Limited Country to Confront Unprecedented Pandemic - Rayamajhee, Binod; Pokhrel, Anil; Syangtan, Gopiram; Khadka, Saroj; Lama, Bhupendra; Rawal, Lal Bahadur; Mehata, Suresh; Mishra, Shyam Kumar; Pokhrel, Roshan; Yadav, Uday Narayan (Frontiers in Public Health, 2021)
COVID-19 caused by SARS-CoV-2, first reported in Wuhan China is now a pandemic has affected over 200 countries and territories in our living planet. As other hundreds of countries around the globe, Nepal is also severely affected by it, with increasing number of confirmed cases and casualties in recent days even after 8 months of first case detected in China. Till August 16 2020, there are over 26,660 confirmed cases of COVID-19 in Nepal with 17,335 recovered cases and 104 deaths. Here, we have compiled the public data available from the Ministry of Health and Population (MoHP), Government of Nepal and analyzed the data of 104 deceased COVID-19 patients using IBM SPSS (Version 25.0). Figures and maps were created using OriginLab (Version 2018), and QGIS (Version 3.10.8).The mean age of 104 COVID-19 death cases is 50.99 ± 18.74 years. Most of the cases are reported from Province No. 2 which has open boarder with the northern part of India, and from Bagmati Province where the federal capital city lies. Among all fatal cases, male accounted for 77.9%, and 18.3% of deceased patients were returnee from India where 52.9% of deceased patients were 50 years or younger. Respiratory illness (53.85%,) followed by diabetes (21.2%,) and chronic kidney disease (14.4%,) were most common comorbid conditions associated with COVID-19 deaths in Nepal. Despite the government efforts for the past eight months when first case was detected ,the responses so far by the Government of Nepal have been insufficient. As the government eased the lockdown in July 2020, Nepal is facing flooding cases of COVID-19 in recent days. Therefore, if no aggressive actions are taken, this epidemic in Nepal is likely to result in significant morbidity and mortality. The best way to curb the effect of ongoing COVID-19 pandemic in Nepal is to increase the testing and tracing and isolating capacity, and to set up good quarantine centers throughout the nation. In addition, health literacy campaign, a good care of older people and those with comorbidity will help effective management of the ongoing pandemic in resource-limited country like Nepal.